Reaching the unreached: Mobile surgical camps in a remote village of Himachal Pradesh - Sonal Bathla; George Verghese; Vinod Kalla; T C Sharma; Subrat Dam; Nirmala Agarwal; Sweta Balani; Priti Arora Dhamija; Deepa Agarwal; Praveen Kumar (Wolters Kluwer Medknow Publications, 2014)
Aims: The aim was to study the epidemiological factors responsible for pelvic organ prolapse (POP) in poor women of the remote village Shillai, do their POP quantification staging, to study the variety of surgeries conducted in mobile surgical camps in this area. Materials and Methods: Retrospective analysis of surgeries conducted in five mobile surgical camps in Shillai, Himachal Pradesh from 2009 to 2013, under "Project Prolapse". Results: A total number of surgeries conducted in five camps from 2009 to 2013 were 490 including 192 gynecological surgeries. Eighty-two percent of gynecological surgery was conducted for POP. Poor nutritional status (mean weight 41.1 kg), multiparty (mean 3.5), early marriage (mean age 18.2 years), unassisted home deliveries (100%), premature bearing down (23.8%), early postpartum resumption of strenuous activity (54.7%) and smoking (33%) contribute to the high incidence of POP. Anterior compartment prolapse was seen in 99% of patients undergoing surgery while posterior compartment prolapse was seen in 4% of patients. Vaginal hysterectomy with anterior repair with culdoplasty was the most common procedure performed (73.4%), and vault suspension was done in 3.6% subjects. The complication rate was negligible. Conclusion: Uterovaginal prolapse is not only socially embarrassing and disabling; its surgical treatment is complex and costly too. The free mobile surgical camps under "Project Prolapse" in Shillai, Himachal Pradesh has provided relief to old neglected, disabled women suffering from prolapse in this remote village. Parallel counseling of women and dais for safe hospital delivery and training subordinates in prolapse surgery may help in addressing the problem of POP in this area in the long run.